Thrombus Imaging Characteristics and Outcomes in Acute Ischemic Stroke Patients Undergoing Endovascular Treatment. Issue 8 (August 2019) - Dutra, Bruna G.; Tolhuisen, Manon L.; Alves, Heitor C.B.R.; Treurniet, Kilian M.; Kappelhof, Manon; Yoo, Albert J.; Jansen, Ivo G.H.; Dippel, Diederik W.J.; van Zwam, Wim H.; van Oostenbrugge, Robert J.; da Rocha, Antônio J.; Lingsma, Hester F.; et al.
Abstract : Background and Purpose—: Thrombus imaging characteristics have been reported to be useful to predict functional outcome and reperfusion in acute ischemic stroke. However, conflicting data about this subject exist in patients undergoing endovascular treatment. Therefore, we aimed to evaluate whether thrombus imaging characteristics assessed on computed tomography are associated with outcomes in patients with acute ischemic stroke treated by endovascular treatment. Methods—: The MR CLEAN (Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands) Registry is an ongoing, prospective, and observational study in all centers performing endovascular treatment in the Netherlands. We evaluated associations of thrombus imaging characteristics with the functional outcome (modified Rankin Scale at 90 days), mortality, reperfusion, duration of endovascular treatment, and symptomatic intracranial hemorrhage using univariable and multivariable regression models. Thrombus characteristics included location, clot burden score (CBS), length, relative and absolute attenuation, perviousness, and distance from the internal carotid artery terminus to the thrombus. All characteristics were assessed on thin-slice (⩽2.5 mm) noncontrast computed tomography and computed tomography angiography, acquired within 30 minutes from each other. Results—: In total, 408 patients were analyzed. Thrombus with distal location, higher CBS, and shorter length were associated with better functional outcome (adjusted common odds ratio, 3.3; 95% CI, 2.0–5.3 for distal M1 occlusion compared with internal carotid artery occlusion; adjusted common odds ratio, 1.15; 95% CI, 1.07–1.24 per CBS point; and adjusted common odds ratio, 0.96; 95% CI, 0.94–0.99 per mm, respectively) and reduced duration of endovascular procedure (adjusted coefficient B, −14.7; 95% CI, −24.2 to −5.1 for distal M1 occlusion compared with internal carotid artery occlusion; adjusted coefficient B, −8.5; 95% CI, −14.5 to −2.4 per CBS point; and adjusted coefficient B, 7.3; 95% CI, 2.9–11.8 per mm, respectively). Thrombus perviousness was associated with better functional outcome (adjusted common odds ratio, 1.01; 95% CI, 1.00–1.02 per Hounsfield units increase). Distal thrombi were associated with successful reperfusion (adjusted odds ratio, 2.6; 95% CI, 1.4–4.9 for proximal M1 occlusion compared with internal carotid artery occlusion). Conclusions—: Distal location, higher CBS, and shorter length are associated with better functional outcome and faster endovascular procedure. Distal thrombus is strongly associated with successful reperfusion, and a pervious thrombus is associated with better functional outcome. Abstract : Supplemental Digital Content is available in the text.